Organ Donation and Transplantation: Public Awareness and Willingness in Karachi Pakistan - Ghazala Nasim Pasha, Saba Pario, Murad Qadir, Rafat Murad, Adeena Habib Siddiqui, Hina Gul (Pakistan Journal of Medical & Health Sciences, 2023)
Background: High prevalence of chronic diseases is leading to increased number of “end organ damage”. The one and only effective treatment is to replace nonfunctional organs with functional ones, donated by live or dead donors. In Pakistan, like global scenario, large numbers of patients are waiting in the queue to receive organs from donors because of increased organ failures. This study investigated the people awareness and response regarding organ transplantation. Objectives: 1 To find the causes of deficient organ donation. 2 To explore ways for providing correct information, which can increase the supply of donated organs. Method: Cross sectional study conducted on a sample size of 402 adults selected from general population of Karachi. Study was done from 28th June, 2022 to 1st December 2022. Analysis of data was done on SPSS version 23. Results: Among 402 participants, awareness about organ donation and transplantation was found in 384 (95%). Cadaveric organ donation awareness was in 53%. The source of information was Internet / social media. Knowledge of OD from Educational Literature in males 28 (20%) in females 44 (18%). Television males 37 (27%), females 32 (13%). Conclusion: Willingness to donate is dependent on knowledge of different aspects like law, religion, trading of organs and opinion of family members. Health education is needed as a part of MBBS, curriculum Misunderstandings and misconceptions are to be cleared through media campaign. Keywords: Organ transplantation, Organ donation, Organ failure, Organ recipient, Cadaveric.